KERAGAAN PRODUKSI BEBERAPA VARIETAS KACANG PANJANG DI DATARAN RENDAH - Aisyah Humairoh; rajiman rajiman; Agus Wartapa (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2026)
The study aimed to determine the production performance of several long bean varieties in the lowlands. The study was conducted from September to December 2025 at the Agro Nusantara Prima Garden in Sendangtirto Village, Berbah Subdistrict, Sleman Regency, Yogyakarta Special Region. The study used a RAKL test design with 4 replications. The treatments consisted of varieties: KP ANP 01, Pertiwi, RKP 15, and Merah Putih Super. Observation data were analyzed using analysis of variance and continued with a 5% HSD test. The results showed that the variety treatment significantly affected the main parameters, namely pod weight per plant, number of pods per plant, pod length, storage capacity, leaf size and stem diameter, and productivity. However, it did not significantly affect the age at flowering. KP ANP 01 has a pod weight per plant of 762.33 grams, the number of pods per plant is 41.68, the pod length is 64.86 cm, the shelf life is 6.84 days, the leaf length is 15.45 cm, the leaf width is 9.59 cm, the stem diameter is 0.75 mm and the age of flowering is 38.50 days. The KP ANP 01 variety has advantages in the form of pod weight per plant, productivity and longer shelf life.